Event-shape and multiplicity dependence of freeze-out radii in pp collisions at √s = 7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Beck, Hans; Borissov, Alexander; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; et al. (Journal of high energy physics, 2019)
Two-particle correlations in high-energy collision experiments enable the extraction of particle source radii by using the Bose-Einstein enhancement of pion production at low relative momentum q ∝ 1/R. It was previously observed that in pp collisions at s$$ \sqrt{s} $$= 7TeV the average pair transverse momentum kT range of such analyses is limited due to large background correlations which were attributed to mini-jet phenomena. To investigate this further, an event-shape dependent analysis of Bose-Einstein correlations for pion pairs is performed in this work. By categorizing the events by their transverse sphericity ST into spherical (ST > 0:7) and jet-like (ST < 0:3) events a method was developed that allows for the determination of source radii for much larger values of kT for the first time. Spherical events demonstrate little or no background correlations while jet-like events are dominated by them. This observation agrees with the hypothesis of a mini-jet origin of the non-femtoscopic background correlations and gives new insight into the physics interpretation of the kT dependence of the radii. The emission source size in spherical events shows a substantially diminished kT dependence, while jet-like events show indications of a negative trend with respect to kT in the highest multiplicity events. Regarding the emission source shape, the correlation functions for both event sphericity classes show good agreement with an exponential shape, rather than a Gaussian one.